2019
DOI: 10.1016/j.jseaes.2019.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Structural controls on polyphase hydrothermal dolomitization in the Kinta Valley, Malaysia: Paragenesis and regional tectono-magmatism

Abstract: In the eastern side of the Malay Peninsula, thick successions of limestone formations preserve important records of the Mesozoic and Cenozoic tectonic events. Here we investigate the strata-and fracture-bound hydrothermal dolomites in the Palaeozoic carbonates of the Kinta Valley, western Peninsular Malaysia. Based on their textural and morphologic characteristics, structural relationships with the host rock, different facies types, and associations with hydrothermal calcite and low-grade metamorphic marble, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 95 publications
(196 reference statements)
1
10
0
Order By: Relevance
“…K The brecciated dolomites in P6 facies are cut through by calcite veins. L Dolomite crystals being severely sheared and tectonized again reflects the recurrence of tectonic events (adapted from Ramkumar et al 2019) statistical analyses examined 33 geochemical constituents for their quantitative measurements using SPSS software, utilizing a standardized dataset with uniform measurement units and PAAS-normalized REE data. Statistical techniques such as correlation and factor analysis were also performed within the same facies and among various facies, grouping according to elemental compositions, the variance of data and dominance of respective elements over total variance (Ramkumar et al 2006(Ramkumar et al , 2013(Ramkumar et al , 2014.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…K The brecciated dolomites in P6 facies are cut through by calcite veins. L Dolomite crystals being severely sheared and tectonized again reflects the recurrence of tectonic events (adapted from Ramkumar et al 2019) statistical analyses examined 33 geochemical constituents for their quantitative measurements using SPSS software, utilizing a standardized dataset with uniform measurement units and PAAS-normalized REE data. Statistical techniques such as correlation and factor analysis were also performed within the same facies and among various facies, grouping according to elemental compositions, the variance of data and dominance of respective elements over total variance (Ramkumar et al 2006(Ramkumar et al , 2013(Ramkumar et al , 2014.…”
Section: Methodsmentioning
confidence: 99%
“…Fig. 1 A-D Regional geological setting, structural trends and location of the study area (modified after Ramkumar et al 2019). A Simplified regional topographic map showing the regional setting and location of the Kinta Valley in western Malaysia.…”
Section: Regional Geological Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…Ali et al, 2016;François et al, 2017;Sautter et al, 2017). They likewise suggested that moving liquids in the Late Cretaceous brought a significant remagnetiz ation of Palaeozoic and Triassic rocks (Metcalfe, 1993(Metcalfe, , 2013Richter et al, 1999;Ramkumar et al, 2019). In the Main Range granitoids, during Late Cretaceous, thermal episodes may be presented by huge acidic or felsic fluids stopping up existing structure sets (Sautter et al, 2017).…”
Section: Geology and Tectonics Of Kinta Valleymentioning
confidence: 99%